Disability sport profile of Ghana: evolution, policies, politics and participation barriers - Charway, Derrick; Osei-Nimo Annor, Dennis; Banda, Davies (Frontiers in Sports and Active Living, 2025)
The profile analyses the landscape of disability sport in Ghana, tracing its historical evolution and contemporary challenges. Alongside legislative advancements and the dedication of various stakeholders, an increase in the persons with disability population has been observed. Based on data from the Ghana Statistical Service census, this demographic rose from 737,743 in 2010 to 2,098,138 in 2021, constituting 3% and 8% of the Ghanaian population in those respective years. Nevertheless, significant barriers to the mainstreaming of disability sport persist. The analysis delves into the interplay of cultural norms, government policies, and collaborative efforts in shaping the trajectory of disability sport in the country. Insights into the population of persons with disabilities and their engagement in sport offer a foundation for discussion. Further, an analysis of the roles of key state and non-state organisations, alongside international partners, emphasises the need to move from symbolic implementation to genuinely inclusive implementation. Contemporary issues such as political infighting, inadequate funding, gender dynamics, limited media coverage, exploitation of disability sport and systemic neglect continue to hinder progress. The profile underscores the urgent need for sustained policy implementation, increased investment, and a more inclusive and collaborative approach to secure a promising future for disability sport in Ghana.